Comparison of Knowledge, Attitude and Practice About Colorectal Cancer Screening Between University Faculty Members and High School Teachers in Shiraz, Iran - Sulmaz Ghahramani; Pegah Jahani; Gholamreza Abdollahifard (Shiraz University of Medical Sciences, 2015)
Background: Teachers and university faculty members can play key role in raising the awareness and knowledge of the populations and potentially change their attitude and behavior regarding CRC. Thus considering the important role played by this group and regarding the increasing rate of CRC, the present study attempted to evaluate the basic knowledge of high-school teachers and university faculty members and their attitude and practice in connection with CRC screening test. Objectives: The aim of this study was to compare the knowledge, attitude and practice about Colorectal Cancer Screening between University Faculty members and High School teachers in Shiraz, Iran. Materials and Methods: This cross-sectional study comprised 832 subjects with high education level. Use of a sample size formula indicated the need for at least 770 participants; a population goal was set at 831 individuals. The study involved 424 males (212 high school teachers and 212 faculty members) and 417 females (206 high school teachers and 211 faculty members). Stratified random sampling method was carried out proportionally to population size in each group. Questionnaires were completed via face to face interview. Data were analyzed using SPSS.V.13. Results: Mean scores for knowledge of male faculty members (3.47 ± 1.39) and female teachers (4.09 ± 1.51) were greater than female faculty members (2.36 ± 1.28) and male teachers (2.65 ± 1.96). Male faculty members had higher mean scores for attitude (3.00 ± 1.61) than that of female teachers (3.00 ± 2.09). A significant difference was observed in mean knowledge scores (P = 0.001) of female teachers with different academic degrees, but not in regard to attitude (P = 0.89). Conclusions: This study showed no acceptable level of knowledge, attitude and practice about screening of colon cancer among faculty members and teachers from different areas of Shiraz. This calls for further attention paid by health professionals and other authorities concerned with regard to providing the population under study with necessary information about colon cancer screening.